Analysis of Inlet and Outlet Wastewater Quality in WWTP Djoelham Regional General Hospital Binjai City - Lailatul Mardhiyah; Meutia Nanda (PROMOTOR, 2023)
Hospitals produce quality liquid waste that is not by the standard value of quality standards that can pollute the environment. Indonesia is estimated to produce 48,985.70 tons of hospital liquid waste/per day. This study aims to determine the quality of inlet and outlet wastewater as well as the methods used by the Wastewater Treatment Plant (WWTP) of Djoelham Hospital, Binjai City. This study used qualitative types with observational methods. The research sample was taken from two points, namely the inlet point and the WWTP outlet point with BOD, COD, TSS, and pH parameters. Sampling technique using Composite Sampling. Data processing and analysis is carried out by statistical means. As well as data presented in the form of tables and line graphs. This research was conducted at Djoelham Hospital in Binjai City from March to May 2023. The results showed that the quality of wastewater in the parameters of BOD, COD, TSS, and pH in the inlet basin was by the quality standards of the Minister of Environment Regulation Number 5 of 2014, except for the value of TSS parameters in April 31 mg / l and May 35 mg / l. The quality of wastewater in the outlet basin based on the STORET method with a total score of 0 is classified as Class A (very good) or has met the quality standard value of the Minister of Environment Regulation Number 5 of 2014. Based on calculations, the average value of effectiveness of BOD (13.53%), COD (11.22%), and TSS (49.79%) was obtained. The WWTP method uses 2 methods, the aerobic and anerob methods. It is expected that the hospital will check the quality of inlet and outlet wastewater at least once every 1 month by PERMENLH Number 5 of 2014.